Perkembangan Anak ditinjau dari Teori Konstruktivisme - Sunanik, Sunanik (SYAMIL: Journal of Islamic Education, 2014)
Education can be viewed as a lifelong learning process which is planned and organized. Constructivist theory states that every person develop through a series of levels that must be taken, but childhood can help students to prepare and get new understanding through activities and social interactions. This method gives the teachers views about learning readiness. Once they understand how a kid knows the world, so they can plan the experience in order to deepen and strengthen their knowledge. Children who learn are not only imitated or reflected with the taught or what he read, but also to create understanding. When children interact with their environment, they build schemes variety, arrangements or patterns. This is the basis for more complex structures in the development of the mental activity. the implications of the theory of constructivism in early childhood education are as follows: (1) the purpose of education according to the theory of constructivism learning is to produce individuals or children who have ability to think or solve any problems, (2) curriculum is designed in a situation that enabling knowledge and skills can be constructed by learners. In addition, training is often done through a problem solving group to analyze problems in their life, and (3) the learners are always expected to be active and can find a way of learning better